The Impact of Marketing Mix On Customer Loyalty Towards Plaza Indonesia Shopping Center - Sylvia Tjan (iBuss Management, 2015)
As Jakarta is one of the cities with the highest numbers of shopping centers in the world as well as the most populous city in Southeast Asia, it is no surprise if the city is packed with buildings, malls, cars, and people. That is one of the reasons why there is Moratorium of shopping center in Jakarta. Left with 173 malls standing in Jakarta, they have to compete with what is left, the marketing strategy. Shopping centers compete crazily on their marketing in order to gain the loyalty of the customers, therefore the competition is so tense. To force out the competition, this research is conducted with the aim to find out the impact of Marketing Mix the 7Ps (as one of the most famous marketing tools) on customer loyalty toward Plaza Indonesia shopping center. The data was gathered using simple random sampling by distributing questionnaires to 147 respondents. Then, the data was analyzed using Multiple Linear Regression Analysis. It is proven that the 7Ps of the Marketing Mix simultaneously has significant impact on customer loyalty toward Plaza Indonesia. However, only product, place, promotion and physical evidence are proven to individually has significant impact on customer loyalty toward Plaza Indonesia. Keywords: Marketing Mix, Customer Loyalty, Shopping Center